Circulating microparticles are associated with plaque burden and cause eNOS uncoupling in patients with carotid atherosclerosis - Han, Xiaowan; Li, Tong; Wang, Tieshan; Wang, Baofu; Li, Yang; Wang, Lei; Lu, Ziwen; Wu, Aiming; Liu, Lisong; Pan, Guozhong; Zhao, Mingjing (Frontiers in Pharmacology, 2022)
Aims: The study aimed to evaluate the correlation of different microparticle (MP) phenotypes with plaque burden and their diagnostic value and preliminarily explore the role of MPs in atherosclerosis (AS). Methods: Carotid intima-media thickness (CIMT) and maximal plaque area in 23 patients with carotid atherosclerosis (CAS) and 22 healthy subjects were measured by ultrasound. Flow cytometry assay measured absolute number of MPs, and receiver operating characteristic (ROC) analysis was used to assess the relationship between plaque burden and MPs. To study the preliminary mechanism of MPs in AS, MPs were administered to 32 male Kunming mice, which were randomly divided into control, CAS, healthy, and tetrahydrobiopterin (BH4) groups. Hematoxylin-eosin staining, immunohistochemistry staining, and western blot were adopted to detect relevant indexes 24 hours after the injection. Results The plasma levels of CD45+ leukocyte-derived microparticle (LMP), CD11a+ LMP, CD11a+/CD45+ LMP, and CD31+/CD42b+ platelet-derived microparticle (PMP) in CAS patients were significantly higher than those in healthy subjects, and were positively correlated with the maximal plaque area. Moreover, the levels of CD11a+ LMP, CD11a+/CD45+ LMP were also positively correlated with CIMT. The area under the ROC curve of the four MPs was 0.689,0.747, 0.741, and 0.701, respectively. Compared with healthy subjects, MPs from CAS patients resulted in a significantly lower expression of endothelial nitric oxide synthase (eNOS) dimer/monomer, and BH4 could improve eNOS uncoupling. Moreover, the level of VCAM-1 in intima in the CAS group was significantly higher than in the other three groups. Conclusions: CD11a+ LMP and CD11a+/CD45+ LMP might be potential biomarkers for CAS prediction. BH4-related eNOS uncoupling occurs in CAS patients, and circulating MPs from them lead to endothelial dysfunction through eNOS uncoupling.